2010
DOI: 10.1007/s13233-010-0613-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compatibilizers on the mechanical properties and interfacial tension of polypropylene and poly(lactic acid) blends

Abstract: The effects of compatibilizers and hydrolysis on the tensile and impact strength, interfacial tension and morphology of the PP/PLA (80/20) blends were investigated. For the PP/PLA (80/20) blends before hydrolysis, the tensile strength of the blends reached a maximum when the polypropylene-g-maleic anhydride (PP-g-MAH) copolymer was added at 3 phr. For the PP/PLA (80/20) blends after hydrolysis, the tensile strength did not change appreciably with the PP-g-MAH content. For the blends with the styrene-ethylene-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 19 publications
2
63
0
1
Order By: Relevance
“…Sangeetha et al reported that impact strength was higher in PLA/SEBS‐g‐MA blends than that in PLA/SEBS, which may be due to the interaction between maleic anhydride groups in SEBS‐g‐MA and carbonyl groups of PLA. SEBS‐g‐MA copolymer is used to toughen many polymers such as polypropylene (PP), high density polyethylene, nylon‐6, nylon‐6,6 and PLA . Yoo et al reported that SEBS‐g‐MA is an effective impact modifier for PP/PLA blends.…”
Section: Introductionmentioning
confidence: 99%
“…Sangeetha et al reported that impact strength was higher in PLA/SEBS‐g‐MA blends than that in PLA/SEBS, which may be due to the interaction between maleic anhydride groups in SEBS‐g‐MA and carbonyl groups of PLA. SEBS‐g‐MA copolymer is used to toughen many polymers such as polypropylene (PP), high density polyethylene, nylon‐6, nylon‐6,6 and PLA . Yoo et al reported that SEBS‐g‐MA is an effective impact modifier for PP/PLA blends.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the addition of compatibilizer to the PP/PLA blends greatly improved tensile strength. They also showed that PP/PLA blends compatibilized with styrene/ethylene/butylene/styrene‐grafted maleic anhydride (MA) showed decreased tensile strength; but they suggested that it could effectively be used as an impact modifier to improve the impact strength of the PP/PLA (80/20) blends 6. Mohamed et al found that the incorporation of polystyrene (PS) in PLA resulted in thermal stabilization of the blends although the final blends were immiscible, confirmed by two independent T g s 7…”
Section: Introductionmentioning
confidence: 99%
“…However, the compounding of MAPP to the PLA/PP 50:50 blend had a slight influence on the flexural modulus and impact strength of the blend. The effect of MAPP on the mechanical properties of the PLA/PP blend was also investigated by Yoo et al [33] in their research. They added MAPP (1, 3, 5, 7 and 10 phr) to the blend PLA/PP 80:20 to improve the compatibility of the blend and studied the properties of the PLA/PP/MAPP blend.…”
Section: Mechanical Properties Analysismentioning
confidence: 96%